Potential repositioning of exemestane as a neuroprotective agent for Parkinson's disease. (3rd June 2017) - Son, Hyo Jin; Han, Se Hee; Lee, Ji Ae; Shin, Eun Jung; Hwang, Onyou
Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterised by selective degeneration of the nigral dopaminergic neurons, and neuroinflammation and oxidative stress are believed to be involved in its pathogenesis. In the present study, we provide data that the synthetic steroid exemestane, which is currently being used to treat breast cancer, may be useful for PD therapy. In BV-2 microglial cells, exemestane activated the transcription factor Nrf2 and induced expression of the Nrf2-dependent genes that encode the antioxidant enzymes NAD(P)H: quinone oxidoreductase 1, haem oxygenase-1, and glutamylcysteine ligase. It also downregulated gene expression of inducible nitric oxide (NO) synthase, lowered the levels of NO and reactive oxygen species, interleukin-1β and tumour necrosis factor-α in lipopolysaccharide-activated microglial cells. In CATH.a dopaminergic neuronal cells, exemestane also induced the same set of Nrf2-dependent antioxidant enzyme genes and provided neuroprotection against oxidative damage. In vivo, the drug protected the nigral dopaminergic neurons, decreased microglial activation, and prevented motor deficits in C57Bl/6 male mice that had been administered with the dopaminergic neurotoxin MPTP. Taken together, the results suggested a utility of repositioning exemestane towards disease-modifying therapy for PD.